FACTORS AFFECTING CUSTOMERS’ PERCEPTION TOWARDS DIGITAL BANKING SERVICES - et. al., Dr. C. B. Pavithra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There is a rapid development in the banking industry. The use of Digital banking has become an integral part in our life. And it is an effective and the most viable tool for creating customer value. Digital banking is the process by which the customers perform their financial transactions digitally without visiting the bank branch. Digital banking has transformed from the banking activities from brick to click. In digital banking customers use laptops, computers, smartphones, other gadgets and digital technology as a substitute for cheques and other paper transactions. Advancement in the computer, smartphones, internet, information and communication technology, the attraction of customers towards digital banking can be done by communicating the benefits of digital banking services. This is a descriptive study, which deals with digital banking services. This paper is aimed to identify the factors affecting the customers’ perception towards digital banking services, to know the satisfaction level and preference towards digital banking services. After developing a structured questionnaire, survey was conducted among 150 digital banking users, Percentage and Factor Analysis were used in this study. The result reveals that respondents of various age groups prefer doing digital banking over traditional banking. The customers perform their digital banking services using their smartphones. Users feel that digital banking is convenient, ubiquitous, instant transfer of funds and they are satisfied with digital banking services. The implications of the study, suggestions to enhance digital banking services and scope for future research is also being highlighted in this study.